A hipótese corpuscular na filosofia de John Locke - Breno Batista Sardenberg (2013)
The main goal of this work is to show, first, that Locke was an adherent of the mechanical corpuscular philosophy an influent conception of the natural world shared by many seventeenth-century philosophers and scientists and, secondly, that that adhesion constitutes a crucial factor in understanding some important aspects of Lockes thought especially the famous distinction between primary and secondary qualities. In order to do that, we strive to make a relatively detailed study concerning that conception: we present the major theses which compose it, its criticism of the philosophical trends to which it was opposed, and the theories developed by some of its most well-known supporters. Then we try to show how Lockes thought is linked to the corpuscular philosophy and to mechanism by his acceptance of some theses of the mechanical philosophy and by his defense of the corpuscular hypothesis as that which provides the most intelligible explanation of the qualities of bodies. Finally we discuss two much debated themes in the secondary literature about Locke: the already mentioned distinction between primary and secondary qualities and the question of the limits of mechanism such as perceived by Locke